RELEVANCE OF RED FLAGS IN THE EVALUATINH THE RISK OF FINANCIAL STATEMENT FRAUD: PERCEPTIONS OF BRAZILIAN INDEPENDENT AUDITORS - Dal-Ri Murcia, Fernando (2008)
The objective of this paper was to identify perceptions of Brazilian auditors regarding the relevance of red flags in evaluating the risk of fraudulent financial reporting. To accomplish this, a questionnaire was designed using six papers as references: American Institute of Certified Public Accountants (2002), Conselho Federal de Contabilidade (1999), Albrecht and Romney (1986), Eining, Jones and Loebbecke, (1997), Bell and Carcacello (2000) and Wells (2005). Together, these works presented a total of 266 red flags. After a thorough comparative analysis, 45 red flags were selected and classified into 6 clusters: organizational structure and environment, sector/industry, managers, economic-financial position, financial reports and independent auditing. The sample is composed of auditors from the Instituto dos Auditores Independentes do Brasil (IBRACON). A total of 33 auditors participated in this research. Findings evidence that 95.56% of red flags presented an “intermediate risk” or “high risk” in the process of detecting fraudulent financial reporting. All 6 clusters also presented an average fraud risk of 3.35 or higher on a 1-5 scale. Keywords: Red flags. Financial statement. Fraud risk. Perception. Independent auditors.